Dimensions of Community-Based Projects in Health Care (International Perspectives on Social Policy, Administration, and Practice,, 2018)
This salient reference grounds readers in the theoretical basis and day-to-day practice of community-based health care programs, and their potential as a transformative force in public health. Centering around concepts of self-determination, empowerment, and inclusiveness, the book details the roles of physicians, research, and residents in the transition to self-directed initiatives and greater community control. Community-focused interventions and methods, starting with genuine dialogue between practitioners and residents, are discussed as keys to understanding local voice and worldview, and recognizing residents as active participants and not simply targets of service delivery. And coverage pays careful attention to training issues, including how clinicians can become involved in community-based care without neglecting individual patient needs. Among the topics covered are: Narrative medicine in the context of community-based practice. Qualitative and participatory action research. Health committees as a community-based strategy. Dialogue, world entry, and community-based intervention. Politics of knowledge in community-based work. Training physicians with communities. Dimensions of Community-Based Projects in Health Care challenges sociologists, social workers, and public health administrators to look beyond traditional biomedical concepts of care and naturalistic methods of research, and toward more democratic programs, planning, and policy. The partnerships described in these pages reflect a deep commitment to patients' lives, and to the future of public health.